1996
DOI: 10.1128/jb.178.12.3585-3593.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and genetic organization of the bacteriocin 31 determinant encoded on the Enterococcus faecalis pheromone-responsive conjugative plasmid pYI17

Abstract: The conjugative plasmid pYI17 (57.5 kb) isolated from Enterococcus faecalis YI717 confers a pheromone response on the host and encodes the bacteriocin 31 gene. Bacteriocin 31 is active against E. hirae 9790, E. faecium, and Listeria monocytogenes. pYI17 was mapped physically by restriction enzyme analysis and the relational clone method. Deletion mutant and sequence analyses of the EcoRI fragment B cloned from pYI17 revealed that a 1.0-kb fragment contained the bacteriocin gene (bacA) and an immunity gene (bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
153
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(162 citation statements)
references
References 42 publications
(39 reference statements)
1
153
1
3
Order By: Relevance
“…However, several class IIa bacteriocins, for example, listeriocin 743A (Kalmokoff et al 2001), bacteriocin 31 (Tomita et al 1996) and enterocin P (Cintas et al 1997) have been found to have a sectype leader. These bacteriocins are assumed to be secreted by sec-dependent exporting pathway.…”
Section: Biosynthesismentioning
confidence: 99%
“…However, several class IIa bacteriocins, for example, listeriocin 743A (Kalmokoff et al 2001), bacteriocin 31 (Tomita et al 1996) and enterocin P (Cintas et al 1997) have been found to have a sectype leader. These bacteriocins are assumed to be secreted by sec-dependent exporting pathway.…”
Section: Biosynthesismentioning
confidence: 99%
“…N-terminal extensions of most lantibiotics and nonlantibiotics are of the so-called doubleglycine type (leader sequence) and are cleaved off concomitantly with export across the cytoplasmatic membrane by dedicated adenosine triphosphate-binding cassette transporters (ABC-transporters) and their accesory proteins Venema et al 1995). However, some class II bacteriocins, such as acidocin B (Leer et al 1995), divergicin A (Worobo et al 1995), bacteriocin 31 (Tomita et al 1996), enterocin P (EntP) , lactoccin 972 , propionicin T1 (Faye et al 2000), and enterolysin A (Nilsen et al 2003), contain N-terminal extensions of the so-called sec-type (signal peptide), which are proteolytically cleaved concomitantly with bacteriocin externalization by the general secretory pathway or sec-dependent pathway (van Wely et al 2001;Herranz and Driessen 2005). Several bacteriocins produced by enterococci, such as enterocins L50 (L50A and L50B), enterocin Q, and enterocin EJ97 (Cintas et al 1998(Cintas et al , 2000Sánchez-Hidalgo et al 2003), have been shown to be synthesized without N-terminal leader sequences, and may represent a new class of bacteriocins with a novel secretion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…E. faecalis FA-2-2 and OG1-10 and E. hirae have been chosen as representative enterococcal strains for the examination and classification of the bacteriocins produced by the clinical isolates in this study. Class 1 types produce the ␤-hemolysin/ bacteriocin (cytolysin) and are active against a wide variety of gram-positive bacteria, including S. aureus (2,15,17,24,46). The ␤-hemolysin/bacteriocin (cytolysin) of pAD1 belongs to class 1.…”
mentioning
confidence: 99%
“…They usually exhibit a relatively narrow spectrum of activity and are produced by a wide variety of grampositive and gram-negative bacteria (27). Bacteriocin production is thought to provide the host strain with an ecological or other selective advantage over other strains.Many Enterococcus faecalis clinical isolates produce a bacteriocin (3, 5), and the bacteriocin is frequently encoded on the E. faecalis pheromone-responding conjugative plasmid (6,14,21,46). Several E. faecalis bacteriocins have been genetically and biochemically characterized (15, 35), including the ␤-hemolysin/bacteriocin (cytolysin) (6,7,18,20,22) and the peptide antibiotics AS-48 (33), bacteriocin 21 (47), and bacteriocin 31 (46), which are encoded by the E. faecalis conjugative plasmids pAD1 (58 kbp), pMB2 (58 kbp), pPD1 (59 kbp), and pYI17 (57.5 kbp), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation